Impact of visual stimulus complexity on associative learning and associated reaction times in migraine patients - Kálmán Tót; Gabriella Eördegh; Noémi Harcsa-Pintér; Adél Papp; Balázs Bodosi; Gábor Braunitzer; János Tajti; Anett Csáti; Attila Nagy (Scientific Reports)
Abstract The semantic complexity and verbalizability of visual stimuli can influence associative learning. The Rutgers Acquired Equivalence Test (RAET) uses semantically rich stimuli (faces and colored fish) to assess associative learning and generalization, while a modified version, the Polygon test, employs simpler stimuli with reduced semantic content (grayscale circles and geometric shapes). Although cognitive alterations are well-documented in migraine patients during interictal periods, the impact of visual stimulus complexity on associative learning and reaction times has not been studied. Forty-one migraine patients without aura completed both the RAET and Polygon tests. Performance metrics included acquisition error ratios, retrieval and generalization error ratios, and reaction times. The two tests were compared using non-parametric statistical methods. Migraine patients demonstrated comparable acquisition performance on the RAET and Polygon test. However, reaction times were significantly longer in the Polygon test across both acquisition and test phases. Retrieval and generalization performance were also similar between tests, despite longer reaction times with semantically reduced stimuli. Migraine patients showed consistent learning performance across visual stimuli of varying semantic complexity. Prolonged reaction times with simpler stimuli suggest increased cognitive demands, potentially mitigated by cortical compensatory mechanisms that maintain learning ability under challenging conditions.